2005
DOI: 10.1186/1465-9921-6-122
|View full text |Cite
|
Sign up to set email alerts
|

A role for airway remodeling during respiratory syncytial virus infection

Abstract: Background: Severe respiratory syncytial virus infection (RSV) during infancy has been shown to be a major risk factor for the development of subsequent wheeze. However, the reasons for this link remain unclear. The objective of this research was to determine the consequences of early exposure to RSV and allergen in the development of subsequent airway hyperreactivity (AHR) using a developmental time point in the mouse that parallels that of the human neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 44 publications
6
39
1
3
Order By: Relevance
“…Baseline R values in normal BALB/c mice were similar to those reported previously (3). Baseline changes in lung function comparable with those we (5) reported previously were found in the current study (data not shown): a significant increase in baseline airway resistance (R) at 2 d.p.i., but not at other time points after infection, as well as nonsignificant increases in Newtonian (central airway) resistance (R N ), tissue damping (G), and tissue elastance (H) at this time point.…”
Section: Effect Of Rsv Infection On Basal Lung Mechanics and Responsisupporting
confidence: 92%
See 1 more Smart Citation
“…Baseline R values in normal BALB/c mice were similar to those reported previously (3). Baseline changes in lung function comparable with those we (5) reported previously were found in the current study (data not shown): a significant increase in baseline airway resistance (R) at 2 d.p.i., but not at other time points after infection, as well as nonsignificant increases in Newtonian (central airway) resistance (R N ), tissue damping (G), and tissue elastance (H) at this time point.…”
Section: Effect Of Rsv Infection On Basal Lung Mechanics and Responsisupporting
confidence: 92%
“…Unlike whole body plethysmography, however, it is invasive and so does not permit serial measurements from the same animal. Only a limited number of studies to date have employed the flexiVent to determine the effects of RSV on airway function in mice (3,27,42), and no previous studies have evaluated ␤-agonist responses in RSV-infected animals using this system.…”
Section: Discussionmentioning
confidence: 99%
“…5A) and were similar to those reported previously (1). Likewise, exposure to nebulized terbutaline had no effect on baseline total lung resistance values in either saline-or poly(I:C)-treated mice (Fig.…”
Section: Intranasal Exposure To the Double-stranded Rna Analog Poly(isupporting
confidence: 90%
“…For assessment of ␤-agonist responsiveness, a second, age-matched, group of female mice was evaluated in parallel for each treatment condition. As in previous studies (55), initial baseline measurements of lung function with nebulization of saline were followed by exposure to the nebulized ␤-agonist terbutaline (100 M), then increasing doses of methacholine (1,10,20, and 50 mg/ml), with a further dose of ␤-agonist between each dose of methacholine. Average values of 10 total lung-resistance measurements at each methacholine or terbutaline dose were thereby obtained, and percent changes from baseline were calculated, as above.…”
Section: Methodsmentioning
confidence: 99%
“…TNF-a is known as a potent mediator of inflammation and plays a key role during the inflammatory responses of hRSV bronchiolitis (Becnel et al, 2005;McNamara et al, 2004;Morrison et al, 2007). TNF-a may play a protective role in RSV infection (Neuzil et al, 1996).…”
Section: A F G Antonis and Othersmentioning
confidence: 99%